453 Biological responses to non-coated and coated steroidal implants containing equal doses and ratios of trenbolone acetate and estradiol benzoate in beef steers. (7th December 2018) - Smith, Z; Baggerman, J; Kim, J; Wellmann, K; Johnson, B
Abstract: Predominately Angus steers (n = 24; initial BW = 435 ± 28.3 kg) were used to evaluate non-coated and coated implants containing equal amounts of trenbolone acetate (TBA; 200 mg) and estradiol benzoate (EB; 28 mg) in finishing steers. Treatments were no implant (NI ), non-coated (NC ; Synovex-PLUS; Zoetis, Parsippany, NJ) and coated (CI ; Synovex-One Feedlot) implant. There were 2 pen replicates per treatment (n = 4 steers/pen). Longissimus (LM) biopsies, blood, and BW were collected before feeding on d 0, 14, 28, 56, 84, 112, and 133. Androgen receptor ( AR ), estrogen receptor-α ( ER-α ), G-protein coupled receptor 30 ( GPR30 ), IGF-I, and IGF-I receptor ( IGF-IR ) mRNA expression in LM was determined by RT-qPCR using two housekeeping genes. Sera was analyzed for estradiol-17β (E2 ), IGF-I, 17β-trenbolone (TbOH), and urea-N (SUN). Data were analyzed as repeated measures for a completely randomized design; α of 0.10 determined significance. No implant × day interaction was detected ( P ≥ 0.20) for any genes. Coated implant increased ( P < 0.10) GPR30 expression over NI and NC (0.29, 0.36, and 0.47 ± 0.027 arbitrary units for NI, NC, and CI, respectively). In LM, CI had greater ( P < 0.10) IGF-I in LM over NI; NC was intermediate ( P > 0.10; 0.24, 0.28, and 0.34 ± 0.020 arbitrary units for NI, NC, and CI, respectively). An implant × day interaction ( P ≤ 0.10) for E2, IGF-I, and SUN was detected; implants elevated ( P ≤ 0.10) E2, IGF-I and decreased SUN. Differing payout characteristics did not influence AR, ER-α or IGF-IR . Coated implants altered GPR30 ; increasing IGF-I in LM that is critical for proliferation and differentiation of satellite cells. The potential to further enhance lean accretion in steers, fed longer periods, is improved by CI as compared to NI.